Evaluasi Jaringan Pipa Distribusi Perumda Air Minum Tirta Agung Pada Sistem Tuk Ngasinan Kecamatan Pringsurat Kabupaten Temanggung - Susanto, Ivan Setyawan; Nugroho, Budiono; Muhammad, Nicko Fadhil (Journal Innovation of Civil Engineering (JICE), 2024)
Simulation results using the EPANET 2.0 program indicate that in the year 2023, the large average demand flow is 30.47 liter/sec, and in the year 2038, it increases to 49.44 liter/sec, while the existing flow is only 25 liter/sec. Therefore, Tuk Ngasinan requires an additional flow. The existing hydraulic conditions in the Tuk Ngasinan network system still have many areas that do not meet the criteria. Some criteria analyzed include residual pressure, velocity, and unit head loss. During peak hours, there are still several service blocks with residual pressure below the criteria. Meanwhile, during minimal usage hours, many service blocks have pressures above the criteria. The water flow velocity in the pipes also falls below the minimum criteria for many pipes. Additionally, there are still many pipes with unit head loss above the criteria, causing significant energy loss in pipe flow. Keywords: Clean Water; Evaluation; Pipe Network; Residual Pressure; EPANET.